Pelatihan administrasi perkantoran untuk tenaga kependidikan - Dwihartanti, Muslikhah; Kumoro, Joko; Siti Umi Khayatun, Mardiyah; Kistiananingsih, Isti; Nuning Siwi , Utami; Marini, Marini; Wiwik , Ismawati; Yudha Pria, Wibawa; Dina Dwi , Septiandari; Priska Sinta , Dewi; et al. (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2022)
The activities community service is aimed at giving their knowledge and skills about administrative office buildings, especially the ones about correspondence and records for education staff Methods used in activities devoted to the community include: 1. talk, a method of talk used to convey matter related the theory correspondence and the concept of management archive manually and electronically. 2) discussion, a method of discussion done to dig the problem often faced by participants in school, especially dealing with correspondence and the concept of management archive manually and electronically, 3) practice, this method used to give opportunity to participants practice material that has given related correspondence, management archive manually and electronically in school. The results of the activities of the PPM, namely: (1) office administration training activities have been implemented well to produce educators who numbered 25 persons or 83.33%; (2) the process of practice making correspondence service generates a service letter template can be used on school work (3) archival practices Process generates classification archives that can be modified to suit the needs of the school; (3) identified that the ability of the correspondence department participants PPM increased through measurement of the material using a questionnaire about understanding everything expressed very familiar and understand; (4) Identified that the ability of archival service of participants increased through PPM measurement on understanding the material using a questionnaire stating everything is very familiar and understand.